International Legal Instruments as the Rule of the Game for the Trade in COVID-19 Vaccine - Nynda Fatmawati Octarina; Faizin Rahmadi Akbar; Mardika Mardika (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This article discusses international legal instruments that guide the trade in COVID-19 Vaccine. After efforts to discover and develop COVID-19 Vaccine which in fact are in favor of developed countries and high-tech countries as well as rich countries and high-income countries, and then this condition continues to have an impact on the distribution and trade stages resulting in difficulty in accessing the COVID-19 Vaccine fairly and equitably for developing countries and least-developed countries. Tracking international legal instruments from upstream to downstream have been needed to form a comprehensive mindset and find the right of rule of the game of trade in COVID-19 Vaccine. Finally, it was found that various of international legal instruments in form of international agreement that were closely related to the trade in COVID-19 Vaccine is already available, as well as being able to frame the interest of developing countries and least-developed countries on a reasonable basis, that is the occurrence of a national health emergency due to the COVID-19 disease. The principle of pacta sunt servanda must be used as a basic reason that binding all world countries to obey and comply with the contents of international agreement in accordance with the legal will of the competent authorities through the ratification process of that international agreement.